PRELIMINARY EXPERIMENTAL DATA ON TRACE-ELEMENT PARTITIONING BETWEEN TOURMALINE AND SILICATE MELT - van Hinsberg, V (2011)
Tourmaline is a ubiquitous accessory mineral in magmatic deposits, especially those of evolved compositions. It displays a high compositional sensitivity to the composition of its host environment, as well as pressure, temperature and f(O2). These characteristics make tourmaline an ideal monitor of the physical and chemical conditions in its host silicate melt. Of particular interest is its potential to record the trace-element signature of the melt. However, to read this record requires knowledge of the partitioning behavior of trace elements between tourmaline and melt. Here, I present preliminary results of a partitioning experiment between tourmaline and a H 2O- and borosilicate-saturated melt at 800°C and 7.5 kbar, in the presence of B-bearing olivine, hercynitic spinel and ilmenite. Calculated partition-coefficients are invariably close to unity, which shows that tourmaline is unable to significantly fractionate trace elements. Partitioning is systematic and agrees with predictions based on lattice-strain theory, which allows element valence and element site-occupancy to be determined from partitioning data. I conclude that the limited range in partition coefficients results from the diversity of lattice sites in the tourmaline structure, which accommodates trace elements of widely different charge and radius. The composition of tourmaline thus can directly record the compositional signature of its host melt.